2021
DOI: 10.35508/nukleus.v8i2.4237
|View full text |Cite
|
Sign up to set email alerts
|

PENAMBAHAN LARUTAN DAUN BINAHONG DALAM AIR MINUM TERHADAP KUALITAS FISIK DAGING AYAM BROILER FASE FINISHER (Addition of binahong leaf solution in drinking water on physical quality of finisher phase of broiler chicken)

Abstract: This study aims to examine the effect of giving a solution of binahong leaves (Anredera cordifolia) in drinking water on the physical quality of broiler chicken meat finisher phase. A total of 72 broiler chickens strain CP 707 produced by PT Charoen Phokphan Indonesia. This study used a completely randomized design (CRD) with 4 treatments and 6 replications. The treatments consisted of R0: drinking water without binahong leaf solution, R1: drinking water + 20 ml of binahong leaf solution/liter of water, R2: dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The dose of binahong leaf extract could be administered up to 150 mg/kg of body weight without impacting live weight, carcass weight, or carcass percentage. Abraham et al [59] studied binahong leaf extract in broiler finisher diets and found that doses of 20, 30, and 40 ml of binahong leaf extract per liter of water did not improve meat quality.…”
Section: Binahong For Livestock Health and Productivitymentioning
confidence: 99%
“…The dose of binahong leaf extract could be administered up to 150 mg/kg of body weight without impacting live weight, carcass weight, or carcass percentage. Abraham et al [59] studied binahong leaf extract in broiler finisher diets and found that doses of 20, 30, and 40 ml of binahong leaf extract per liter of water did not improve meat quality.…”
Section: Binahong For Livestock Health and Productivitymentioning
confidence: 99%